Pelatihan dan Pendampingan Jumantik Dalam Upaya Pencegahan DBD pada Siswa SMPN 12 Kota Tanjungpinang - Samosir, Kholilah (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2022)
Pinang Kencana Village is an area that is prone to dengue fever with a population of 47,509 people. In 2017 the Pinang Kencana Village occupied the highest dengue cases as many as 52 people. Every year, Pinang Kencana Village is an area that has the highest dengue cases. This is partly influenced by the behavior that often accommodates clean water during the rainy season and in the summer and is also added to the clean water reservoir in the Pinang Kencana sub-district school that does not have a lid so that it can cause the development of Aedes Sp mosquitoes. DHF transmission does not only occur in the neighborhood, but also in schools. Schools are one of the potential places that can be a breeding ground for Aedes mosquitoes, so they can become places for dengue transmission. Places that can be a breeding ground for mosquitoes in schools include water reservoirs, school toilets, flower pots, etc. And the school is also a place where a group of people gather on a regular basis which takes place almost every day, so that it becomes one of the priority places for periodic monitoring of the presence of larvae so that they do not become a source of dengue transmission.